2019
DOI: 10.1097/cm9.0000000000000197
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan does not reduce the mortality of critically ill adult patients with sepsis and septic shock

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Randomized controlled studies of levosimendan versus either inotropic drugs or placebo for the treatment of sepsis or septic shock were included in the second recent meta-analysis. Feng and colleagues [ 27 ] identified 20 such trials that enrolled an aggregate of 1467 patients (levosimendan, n = 738; control, n = 729). Findings very similar to those of Liu et al were documented, with indications of improved cardiac function in the levosimendan group, plus reduction in serum lactate, but no robust impact on mortality.…”
Section: Septic Shockmentioning
confidence: 99%
“…Randomized controlled studies of levosimendan versus either inotropic drugs or placebo for the treatment of sepsis or septic shock were included in the second recent meta-analysis. Feng and colleagues [ 27 ] identified 20 such trials that enrolled an aggregate of 1467 patients (levosimendan, n = 738; control, n = 729). Findings very similar to those of Liu et al were documented, with indications of improved cardiac function in the levosimendan group, plus reduction in serum lactate, but no robust impact on mortality.…”
Section: Septic Shockmentioning
confidence: 99%
“…This may be due to the inclusion of patients with septic shock and cardiogenic shock in addition to those with HFrEF and cardiac surgery. Previous meta‐analyses 126,127 have also shown that levosimendan did not improve mortality rates in patients with septic shock and cardiogenic shock. To identify the subgroup of patients with greater survival benefit from levosimendan treatment, we performed subgroup analyses, which showed (Supporting Information, Figure ) that levosimendan significantly reduced mortality in patients with advanced heart failure.…”
Section: Discussionmentioning
confidence: 92%
“…Авторы комментария к исследованию LeoPARDS пришли к интересному выводу: это исследование не добавляет ничего нового, кроме информации о том, что использование левосимендана у пациентов с сепсисом, с низким системным сосудистым сопротивлением в отсутствие клинических признаков дисфункции миокарда не отличается по клинической эффективности от плацебо [64]. В дальнейшем в серии метаанализов авторам также не удалось выявить достоверной разницы в основных клинических исходах при использовании левосимендана у пациентов с тяжелым сепсисом/септическим шоком по сравнению с добутамином [65] или другими инотропными препаратами [66], однако стоит отметить, что в данные анализы были включены пациенты из исследования LeoPARDS, к интерпретации данных которого нужно подходить с учетом вышеупомянутых ограничений.…”
Section: сепсисunclassified